Digital Economy Acceleration and the Reconfiguration of Labor Wage Structures within the Indonesian Service Sector - Radna Nurmalina; Muhammad Damas Fatih (Smart International Management Journal, 2026)
The rapid acceleration of the digital economy in Indonesia has substantially transformed the service sector landscape, particularly in shaping labor wage structures. This study aims to examine how digital economy acceleration influences the reconfiguration of wage structures within Indonesia's service sector. A quantitative approach was employed using secondary data obtained from Statistics Indonesia (BPS), the World Bank, and national digital economy reports covering the period 2018–2024. The findings indicate that digitalization has increased the demand for high-skilled labor, leading to higher wage premiums for this group, while low-skilled workers tend to experience wage stagnation. Furthermore, the expansion of the platform-based economy (gig economy) has enhanced labor flexibility but also introduced income instability. Wage disparities across service subsectors, including app-based transportation and digital financial services, have become more pronounced. The study concludes that the acceleration of the digital economy not only improves economic efficiency but also fundamentally reshapes wage structures, potentially widening inequality if not accompanied by effective policies in skill development and adaptive social protection systems.